Diclofenac sodium and dexamethasone co-therapy restores brain neuron-specific enolase (NSE), S-100 Beta and glial fibrillary acid protein (GFAP) proteins in experimental rat’s model: A possible inhibition of P-glycoprotein: Diclofenac and dexamethasone cotherapy - Hamdi, Bushra A.; Amin, Zahra A.; Shareef, Abdul Muhaemn Y.; Al-Bustany, Hazem A. (Cellular and Molecular Biology, 2023)
Non-steroidal anti-inflammatory drugs decrease pain and fever while corticosteroids regulate inflammation and immune response, both are prescribed to reduce inflammation and control pain. The present study aimed to study the effects of their monotherapy and co-administration on the brain tissue structure of experimental rats. P-glycoprotein (PGP), a transporter membrane protein, plays an important role in various physiological and physio-pathological conditions, drug-drug and drug-food interactions, and multi-drug resistance. Male rats were divided into four groups and received normal saline, dexamethasone, diclofenac sodium and their dual therapy respectively, then after one-month rats were sacrificed and brain tissues proceeded for hematoxylin and eosin staining to study their histopathology and immunohistochemically staining of NSE, S100-B and GFAP biomarkers were performed. Additionally, in silico molecular docking studies were conducted to elucidate interactions between PGP and used compounds. Resultsshowed that dexamethasone or diclofenac sodium treatments showed abnormalities like edema, neuronal vacuoles, astrocytes hyperplasia and microglial cells with positive reaction to NSE, S100 and GFAP antibodies while the dual therapy displayed less edema and other signs of damage with negative and weak positive staining of NSE, S100 and GFAP antibodies respectively. The molecular docking showed that there were different affinities toward the involved PGP active site. These interaction results were great with Dexamethasone -9.6 kcal/mol forming hydrophobic interactions with the highest affinity when compared with Diclofenac sodium which gave -8.4 kcal/mol. In conclusion, the side effects of the two types of anti-inflammatory drugs may be minimized through their interactions. However, Molecular Dynamic Simulations studies are required to explain the exact dynamic behaviors and protein-ligand stability.